Pistacia vera L. genotypes; a potential rival for UCB-1 rootstock for cultivating under salt stress conditions. (May 2020) - Raoufi, Ahmad; Rahemi, Majid; Salehi, Hassan; Pessarakli, Mohmmad
Abstract: UCB-1( P. integerrima × P. atlantica ) is considered as a high tolerant hybrid rootstock to salt stress from Pistacia genus that widely used as rootstock for pistachio cultivars. This study was conducted to compare the response of five P. vera salt-tolerant genotypes with UCB-1 under salt stress. The experiment was carried out as a completely randomized design with factorial arrangement and four replications. Eight months old pistachio genotypes namely Akbari, Ahmad-Aghaee, Italiyayi, Ghazvini, Badami, and UCB-1 were subjected to salinity stress at three salinity levels (0.5 (control), 12 and 18 dS m −1 ) for 75 days. In order to select the most tolerant genotypes, some physiological and biochemical factors were measured. Leaf water potential, chlorophyll, and K content decreased while leaf total proline, phenolic content, lipid peroxidation, antioxidant enzyme activities, and Na leaf content increased with raising salinity levels regardless of genotypes. Comparison between genotypes indicated that for most of the measured factors, UCB-1 and Akbari showed better performance comparing to others. However, there was no significant difference between Akbari and UCB-1 regarding salt tolerance that shows the high potential of P. vera genotypes to be used instead of UCB-1. Furthermore, there was no significant difference between Akbari, Ahmad-Aghaee, and UCB-1 in malondialdehyde (MDA) and total phenolic content as well as ascorbate peroxidase (APX) activity. In conclusion, the studied rootstocks can be ordered based on their tolerance to salinity as the following: UCB-1 = Akbari > Ahmad-Aghaee > Italiyayi > Ghazvini > Badami.